A Method for Fabricating Arrays of Nanopatterns with the Feature Size beyond Diffraction Limit. (14th December 2008) - Li, Shuhong; Shi, Lifang; Dong, Xiaochun; Du, Chunlei; Zhang, Yudong
Abstract : A convenient lithographic technique is proposed in this paper, which can be used to produce subdiffraction-limit arrays of nanopatterns over large areas (about several square centimeters). An array of polystyrene spheres (PS) is arranged on the surface of a layer of silver which has a thickness of about tens of nanometers. With the normal illumination light of wavelength 365 nm perpendicular to the substrate, PS can generate an array of optical patterns with high intensity at their contact points with silver. By designing the silver slab, the evanescent waves that carry subwavelength information about the optical patterns are substantially enhanced, while propagating components are restrained. In the photoresist which is on the other side of silver, the optical intensity is redistributed and subdiffraction-limit patterns are obtained after exposure and development. Simulation by finite-difference time-domain (FDTD) and experiments were carried out to verify the technique. The results show that by using PS with diameter of 600 nm, nanopatterns with dimension of less than 80 nm can be obtained.